EARLY DIAGNOSIS OF SEPSIS THROUGH SEPSIS MARKERS AND SEPSIS INDEX THROUGH FLOW CYTOMETRY TECHNOLOGY - Chauhan, Sima; Hansa, Jagadish (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Sepsis is a major medical challenge, and remains a burden by showing minimal symptoms, non-specific manifestation which leads to the high-mortality rate. The major cause of high mortality rate is due to the diagnostic pitfalls. The sepsis mechanism involves immune suppression associated with multiorgan dysfunction, uncontrolled infection, and death. This study aims to use new parameters in diagnosis of sepsis particularly neutrophil CD64 (nCD64), monocyte human leukocyte antigen-DR (mHLA-DR), performed by flow cytometer. Methods: Available diagnostic tools such as blood culture (gold standard) and other tools are time-consuming which leads to death because the treatment is not commenced promptly due to unavailability of quick and accurate diagnostic procedures. To overcome such instances, there are different specific cell surface markers which are introduced to reveal sepsis at the earliest using flow cytometry technique. The newer technique allows determination of different cellular and functional pathological components of sepsis. Using this technology, a newer treatment modality (granulocyte macrophage colony-stimulating factor) can be used to reverse sepsis associated immune suppression. Results: The results suggested that the flow cytometric evaluation of nCD64, mHLA-DR expression assay, seems to be promising as comparison to other tools available for diagnosis. Conclusion: The pilot data suggest that the flow assay, sepsis indexâ€ is a useful assay for diagnosing and discriminating sepsis in adult at intensive care unit settings in comparison to all the available current modalities of sepsis diagnosis. However, there are no other comparable parameters to diagnose early sepsis.